Prevalence and Risk Stratification of Ischemic Heart Disease in Obese Diabetic Populations in Rural Vs. Urban Pakistan. A Clinical Study - Muhammad Zahid Ali Raza, Aamir Siddique, Shaoib Ahmed Zia, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ischemic heart disease (IHD) is a leading cause of morbidity and mortality worldwide, with its burden disproportionately higher in low- and middle-income countries such as Pakistan. Obesity and type 2 diabetes mellitus (T2DM) are major contributors to the development of coronary atherosclerosis, and their coexistence significantly increases cardiovascular risk. However, limited evidence exists comparing rural and urban populations in Pakistan. Objectives: This study aimed to evaluate the prevalence and risk stratification of ischemic heart disease among obese diabetic patients in rural versus urban populations of Punjab, Pakistan. Methodology: A cross-sectional study was conducted at Nawaz Shareef Medical College, Aziz Bhatti Shaheed Teaching Hospital, Gujrat, and Chaudhary Pervaiz Elahi Institute of Cardiology, Wazirabad, from June 2022 to March 2023. A total of 100 obese diabetic patients aged 35–70 years were enrolled consecutively. Demographic, clinical, and biochemical data were collected, and ischemic heart disease was diagnosed using clinical assessment supported by ECG and echocardiography. Risk stratification was performed using the Framingham Risk Score. Data were analyzed using SPSS version 25.0. Results: The overall prevalence of ischemic heart disease was 38.0%. Rural patients had a slightly higher prevalence compared to urban patients (40.4% vs. 35.4%), though the difference was not statistically significant. However, 50.0% of rural patients were categorized in the high-risk Framingham group compared to 35.4% of urban patients (p = 0.022). Urban patients exhibited significantly higher waist circumference (p = 0.021), while rural patients had higher smoking prevalence (p = 0.038) and lower socioeconomic status (p = 0.002). Conclusion: IHD is highly prevalent in obese diabetic populations in Pakistan. While central obesity predominates in urban patients, rural populations face higher overall cardiovascular risk due to socioeconomic disadvantage, smoking, and limited healthcare access. Region-specific preventive strategies are essential to reduce the growing burden of cardiovascular disease. Keywords: Ischemic heart disease, Obesity, Diabetes mellitus, , Cardiovascular risk.